Meningkatkan Hasil Belajar Siswa dengan Metode Critical Incidentp pada Mata Pelajaran Fikih di Sekolah Dasar - Suparlan Suparlan (AS-SABIQUN, 2021)
Critical incident strategy (Important Experience) is a strategy to activate students since the start of learning, namely a strategy in which students must remember and describe their past experiences in accordance with the topic of the material presented. The critical incident strategy (important experience) is a strategy in which students must remember and describe their past experiences that are interesting and related and related to the subject to be delivered, then the teacher conveys the material by connecting the experiences possessed by students. According to the Indonesian dictionary, the result is something that exists (happens) by a job, is successful. Meanwhile, according to R.Gagne, results are seen as internal abilities that belong to people and that people do something. While the understanding of learning is etymologically learning to learn from the word "ajar" which gets the prefix ber and is a verb which has the meaning of trying to gain intelligence.